Factors influencing the international trade of carbon offsets from the destruction of ozone depleting substances - Ascui, Francisco (2014)
Presents the results of collaborative research to better understand the factors influencing the participation of stakeholders from developing countries in ozone depleting substances (ODS) destruction projects to generate credits for carbon markets.